The impact of environmental construction on the spatial configuration of traditional Iranian housing (case study: comparison of Dezful and Boroujerd traditional housing) - Hessari, Pedram; Chegeni, Farhad (Journal of Architecture and Urbanism, 2021)
The cities of Dezful and Boroujerd can be considered a treasure trove of traditional houses in Iran whose social, functional, and cultural roots are reflected in their architectural body. Traditional housing includes and expresses the lifestyles and behavioral systems of its inhabitants. Therefore, by analyzing the spatial structure in different traditional dwellings, we can understand the structural differences in them. The main purpose of this study is to identify and express the structure and spatial differences in traditional housing in Dezful and Boroujerd, which have many differences in terms of environmental structure. This study seeks to answer the question: What are the differences between structural patterns and spatial configuration in traditional housing in Dezful and Boroujerd? The method of this research is generally qualitative and software that includes analytical-descriptive approaches and logical reasoning. First, using observation, field survey, and library studies, the desired maps are obtained and the research parameters such as spatial integrity, visual privacy and control, and access are determined. In the next step, the maps of selected research houses are analyzed and analyzed in Space Syntax software, which is specialized software for space syntax, and the patterns of spatial configuration in traditional houses of Dezful and Boroujerd are expressed. The results show that the permeability and readability of more spaces due to the depth of each space and better spatial perception by individuals in traditional houses in Dezful is more than traditional houses in Boroujerd. In contrast, in traditional houses in Boroujerd, spatial stratification and spatial hierarchy, the creation of public and private layers due to the shape and type of housing, and also environmental security in the residential complex is more than the examples of traditional housing in Dezful.